Tourism geography : - Williams, Stephen (Routledge, 2009)
This second edition of Tourism Geography develops a critical understanding of how different geographies of tourism are created and maintained. Drawing on both historical and contemporary perspectives, the discussion a " which is in three main parts a " connects tourism to key geographical concepts relating to globalization, mobility, new geographies of production and consumption, and post-industrial change. Part I examines how spatial patterns of tourism are formed and evolve through time. Part II offers an extended discussion of how tourism relates to places that are toured, examining physical and economic development, socio-cultural and environmental relations and the role of tourism planning. Part III develops a range of new material for this second edition that considers important contemporary influences upon tourism geographies, including place promotion, new forms of urban tourism, heritage, identity and embodied forms of tourism